Simplifying
k^{2} = k
Solving
k^{2} = k
Solving for variable 'k'.
Reorder the terms:
-1k + k^{2} = k + -1k
Combine like terms: k + -1k = 0
-1k + k^{2} = 0
Factor out the Greatest Common Factor (GCF), 'k'.
k(-1 + k) = 0
#### Subproblem 1

Set the factor 'k' equal to zero and attempt to solve:
Simplifying
k = 0
Solving
k = 0
Move all terms containing k to the left, all other terms to the right.
Simplifying
k = 0
#### Subproblem 2

Set the factor '(-1 + k)' equal to zero and attempt to solve:
Simplifying
-1 + k = 0
Solving
-1 + k = 0
Move all terms containing k to the left, all other terms to the right.
Add '1' to each side of the equation.
-1 + 1 + k = 0 + 1
Combine like terms: -1 + 1 = 0
0 + k = 0 + 1
k = 0 + 1
Combine like terms: 0 + 1 = 1
k = 1
Simplifying
k = 1#### Solution

k = {0, 1}